Palatalization in West Chadic - Russell G. Schuh (Studies in African Linguistics)
Morphological palatalization is a phenomenon whereby palatal articulation (fronting of vowels, adding palatalization as a secondary articulation to consonants, changing alveolars to alveopalatals) is a property associated with an entire morpheme, not with individual segments. Within the Chadic language family, morphological palatalization is best documented in the Biu-Mandara branch, but it has been inherited as a feature in the West branch as well. This paper explores palatalization phenomena in the West Branch that conceivably trace their origin to morphological palatalization. In Miya, morphological palatalization operates much as it does in Biu-Mandara languages, affecting entire morphemes and associating with specific morphological processes. Duwai exhibits remnants of morphological palatalization in certain verb alternations. Bole shows alveolar/alveopalatal variations in specific lexical items that have no local phonological explanation. In Hausa, the origin of palatal consonants has long been a source of controversy. The paper argues that local phonological processes of palatalization cannot account for a large number of the palatals in modern Hausa, a claim that has implications for the analysis of the system of high vowels.